Proporsi Tepung Komposit Kacang Hijau (Vigna Ridiata) dan Sagu (Metroxylon Sagu) pada Pembuatan Cookies - Cindy Edyningrum Akbar; Any Sutiadiningsih; Lilis Sulandari; Ila Huda Puspita Dewi (Pusat Riset dan Inovasi Nasional, 2023)
Mung bean and sago composite flour cookies are cookies made from the main raw material of wheat flour which is composited with mung bean and sago flour to reduce the use of wheat flour and to increase nutritional content. This experiment aims to determine 1) the sensory quality of mung bean and sago composite flour cookies including shape, color, aroma, crispness, crumb, and taste 2) chemical properties based on laboratory tests which include carbohydrates, protein, fat, ash, and fiber 3) the cost of raw materials for mung bean and sago composite flour cookies. This type of research is a factorial experiment. The independent variable was the proportion of mung bean composite flour (35%, 25%, and 15%) and sago (15%, 25%, and 35%) that had gone through the starch calculation stage. The dependent variable is sensory quality which includes shape, color, aroma, crispness, crumb, and taste. The control variables of this study include the type of materials and equipment. Observation data collection technique by means of sensory quality test conducted by 35 panelists. Data analysis used single anova test and continued with Duncan test. The results showed 1) there was an influence on the sensory quality of composite flour cookies which included aroma, crispness, crumb, and taste 2) there was no influence on sensory quality in shape and color 3) the best product had a raw material cost of Rp 8,473/250 grams.